Persepsi Mahasiswa tentang Penggunaan DeepL untuk Menerjemahkan Teks Bahasa Inggris - Fhatur Ananda Sidiq; Syafryadin Syafryadin (STKIP Siliwangi, 2024)
Translation is important in the English as a Foreign Language (EFL) setting since it requires turning the source language into the target language. This study is innovative considering the lack of earlier research in this subject. A descriptive quantitative technique was adopted in this study. Twenty six students of Physical Education was done fill the questionnaire. This in-depth assessment was carried out in order to learn as much as possible about the students' points of view and to determine whether or not their opinion was primarily poor or very good. The results demonstrate that while students using DeepL for translation realise vocabulary limitations, they also accept translation approaches. Beyond Google Translate, DeepL's extensive application, adaptability, and efficiency in word-by-word, phrase-by-phrase, and paragraph-by-paragraph translation tasks make it a crucial component of the translation process. Students' use of dictionaries is impacted by DeepL in varied ways; some overcome sloth, while others get addicted to quick searches. Students actively verify findings and learn grammar, even if they have doubts about DeepL. According to the study, the key to adopting DeepL is resolving vocabulary difficulties and striking a balance between technology and traditional language learning methodologies. In order to develop digital language training methods, it suggests examining DeepL's long-term effects on language learning objectives and proficiency.